CHRISTIAN-BASED CHARACTER EDUCATION MANAGEMENT IN IMPROVING THE QUALITY OF HIGH SCHOOL EDUCATION - Nelita Ernawati Nababan; Rugaiyah; Ucu Cahyana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the management of Christianity-based character education in improving the quality of high school education. The research was conducted at one of the Christian high schools in the Tangerang area. The basis for this research is the increasing need for character strengthening in the midst of the moral crisis of the younger generation due to the impact of the negative influence of globalization, technological developments, and the lack of integration of religious values in the lives of students. This study uses a qualitative descriptive method where data is obtained through observation, interviews and documentation studies. The subjects of the study are the principal, vice principal for curriculum and student affairs, teachers of PAK, BK and PKn, homeroom teachers, students, parents and alumni. The results of the study show that the management of Christian-based character education in schools is well designed through systematic, collaborative, and evaluative management. The planning stage is designed in a systematic, structured, and integrated manner from the center (foundation) which is then integrated into the vision and mission, learning objectives, and appropriate curriculum. The organization is carried out with a whole-school approach, which involves all school residents, namely principals, vice principals, teachers, students, parents and alumni. The implementation stage takes place through curricular, co-curricular, and extracurricular learning, where each activity must integrate Christian values. Other actions taken are with an exemplary approach to life and constructive interpersonal communication. Character education is carried out continuously so as to produce an effective habituation process. Subsequently, at the monitoring and evaluation stage, it is carried out holistically and continuously. There are character rubrics in the report cards, reflective journals of students, and evaluations from teachers and foundations accompanied by follow-up on improving and strengthening the program. This shows that Christianity-based character education contributes greatly to improving the quality of education.